(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Diabetic foot ulcers (DFU) are a common and preventable complication of diabetes mellitus, often associated with low foot care literacy and limited family involvement in community settings in Indonesia. Objective: This study evaluated the effectiveness of a family-centered diabetic foot care education program in improving self-care behaviors, family engagement, health literacy, and quality of life among patients with type 2 diabetes. Methods: A six-month single-group pre–post community-based intervention was implemented at a semi-rural primary healthcare center in Tasikmalaya, Indonesia. Of 84 patient–family caregiver pairs recruited, 77 completed the program. The intervention included structured education, foot care demonstrations and redemonstration, family empowerment sessions, and regular home visits. Quantitative outcomes were measured using validated instruments, while qualitative data were collected through observations and family interviews. Results: Significant improvements were observed in family involvement, health literacy, dietary adherence, physical activity adherence, and quality of life (all p < 0.001). Blood glucose levels showed no significant change. Qualitative analysis identified three themes: increased awareness and confidence in foot care, strengthened family roles and shared responsibility, and perceived barriers to sustained glycemic control. Conclusion: Family-centered diabetic foot care education effectively strengthens self-care behaviors, family engagement, and psychosocial outcomes in community settings. Longer-term and integrated interventions may be required to improve metabolic outcomes.